Cost Performance of Overall Equipment Effectiveness in Manufacturing: The Activity-Based Effectiveness Approach - David, Elmarie (University of the Witwatersrand, Johannesburg, 2024)
This research paper aimed to develop, validate, and implement a structured and replicable method for assessing overall equipment effectiveness (OEE) using a cost-oriented approach known as the Activity-Based Effectiveness (ABE) methodology. Integrating principles from both the Overall Equipment Effectiveness (OEE) and Activity-Based Costing (ABC) methodologies, the proposed ABE methodology offered a systematic framework for evaluating and enhancing organizational performance. By shifting the focus from time-based or percentage-based metrics to cost-based metrics, the ABE approach sought to enhance understanding, benchmarking, and decision-making within organizations. The study adopted a mixed-methods approach, involving two phases of data collection. Firstly, an electronic survey and interview questionnaire were administered to participants employed across various organizational levels within the manufacturing industry. A minimum of 125 participants were surveyed, and the data were analysed using SPSS software. Secondly, the ABE methodology was implemented at a case company operating in the automotive component manufacturing sector, where OEE data were collected over a three-month period from ten different machines. The collected data were analysed using the ABE methodology, with informed consent obtained from the case company and strict confidentiality measures in place. The findings revealed that the implementation of the ABE approach facilitated a clear identification of areas requiring improvement, thereby enhancing understanding, benchmarking, and decision-making processes. However, it should be noted that this study was limited to the implementation of the ABE system within a single case company. While the standardized cost approach implied generalizability, it could not be conclusively verified through this research alone. Additionally, since the case company already had OEE and ABC methodologies in place prior to the study, the full implementation of the ABE system remained untested. Nevertheless, this research offered a practical framework for calculating OEE as a cost metric in a structured manner, thereby supporting organizational effectiveness.
A research report submitted in partial fulfillment of the requirements for the degree of Master of Business Administration to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: Overall Equipment Effectiveness (OEE); Overall Organizational Effectiveness (OOE) Activity- Based Costing (ABC); Capacity Improvement; Performance Improvement; Complex Systems Theory; UCTD; SDG-8: Decent work and economic growth